150 Jahre Periodensystem der chemischen Elemente. Issue 7 (14th October 2019) - Boeck, Gisela
Translation abstract: The International Year of the Periodic System gives reason to describe the most important steps on the way to its establishment. The paper will discuss several classification systems which were developed by precursors. Then the contributions of Lothar Meyer and Dmitri I. Mendeleev will be discussed and compared in more detail. Main emphasis will be given to the work of Meyer because it is less known. Abstract: Das Internationale Jahr des Periodensystems gibt Anlass, die wichtigsten Stationen auf dem Weg bis zu dessen Aufstellung nachzuzeichnen. Es werden einige Klassifikationssysteme von Vorläufern vorgestellt und die Beiträge von Lothar Meyer und Dmitri I. Mendeleev näher untersucht. Schwerpunkt wird dabei auf die weniger bekannten Meyer'schen Arbeiten gelegt.